ENHANCING EFL LEARNING THROUGH MOBILE-ASSISTED LANGUAGE LEARNING IN A NATURE-BASED SCHOOL ENVIRONMENT: A MIXED-METHODS STUDY - Riyadi Ariyanto; Slamet Asari (English Review: Journal of English Education, 2026)
Mobile-Assisted Language Learning (MALL) has been widely implemented in formal classroom settings; however, its application in alternative educational environments such as nature-based schools remains underexplored. This mixed-methods study investigated the effectiveness of MALL in enhancing EFL vocabulary learning, student engagement, and learning motivation in a nature-based school environment in East Java, Indonesia. Thirty-two seventh-grade students participated in a six-week intervention integrating mobile applications, including Quizlet, Google Lens, and digital vocabulary games, with outdoor experiential learning activities. Quantitative data were collected through pre-test and post-test vocabulary assessments and a Likert-scale questionnaire, while qualitative data were obtained through classroom observations and semi-structured interviews. Quantitative data were analyzed using paired-sample t-tests, whereas qualitative data were analyzed thematically. Before conducting inferential analysis, the Shapiro-Wilk test confirmed that the data were normally distributed. The findings revealed a statistically significant improvement in students’ vocabulary achievement after the implementation of MALL, t(31)=8.47, p < 0.001. The mean score increased from 62.31 (SD=8.12) in the pre-test to 81.47 (SD=6.95) in the post-test. The effect size was large (Cohen’s d = 1.87), indicating substantial practical significance. Questionnaire findings also demonstrated high levels of learning motivation (M=4.32), student engagement (M=4.25), and learner autonomy (M=4.18). Qualitative findings revealed that students perceived MALL positively because mobile applications helped them connect English vocabulary with authentic objects encountered during outdoor learning activities. The study concludes that integrating MALL with nature-based experiential learning effectively supports contextualized vocabulary acquisition and learner engagement in alternative EFL educational settings. The findings provide pedagogical implications for EFL teachers seeking to integrate technology-enhanced learning into contextualized outdoor instruction.